Tomada de decisão e equilíbrio de metas conflitantes no gerenciamento de interrupções de voo em empresa de transporte aéreo regular - Fogaça , Lucas Bertelli (2015)
overcoming problems like airport closures, infrastructure issues and unplanned maintenance events. To face such problems, these companies maintain Operational Control Centers (OCCs) that oversee the execution of all planned flight operations and try to accommodate any encountered variability. These OCCs rely on the experience of its decision makers and high technology to evaluate complex scenarios and balance conflicting goals to get to fast and efficient solutions, while trying to preserve the system’s response capability. The objective of this study is to characterize the decision making inside an OCC, facing the challenges to balance conflicting goals in situations of airline disruption management. This research presents a single case study performed inside an airline e that operates around 900 flights per day in Brazil. A systemic mapping of the OCC was performed using the Functional Resonance Analysis Method (FRAM), followed by interviews using the Critical Decision Method (CDM) and at last, an analysis of the effects of the balancing of conflicting goals in the systems response capability facing variability is shown.Points of resilience and organizational brittleness were found in the system. The characterization of the decision making has shown some of the most common problems in challenging scenarios and some of the most used strategies used to overcome them, along with combinations of decisions that influence the systems response capability. The utilization of the FRAM, associated with CDM in the study of decision making showed promise for use in future research in other airlines or even other industries, revealing important implications for training and procedure development.